A novel polyamine-type starch/glycidyl methacrylate copolymer for adsorption of Pb(II), Cu(II), Cd(II) and Cr(III) ions from aqueous solutions. Issue 6 (6th June 2018) - Chen, Youning; Zhao, Wei; Wang, Huan; Meng, Xiaohua; Zhang, Linjie
Abstract : A novel polyamine-type starch/glycidyl methacrylate (GMA) copolymer with a high capacity for the adsorption of heavy metal ions was prepared via graft copolymerization of GMA and corn starch and a subsequent amination reaction between amino group of diethylenetriamine and epoxy group in GMA. The copolymers were characterized by Fourier transform infrared spectrometry, X-ray diffraction and scanning electron microscopy, and adsorption properties on modified starch of Cu(II), Pb(II), Cd(II) and Cr(III) were studied. By analysing the relationship between adsorption capacity and pH, adsorption isotherms and adsorption kinetics, it is proved that the adsorption of the four metal ions is mainly based on the chemical adsorption of coordination. The maximum adsorption capacities of the copolymer were up to 2.33, 1.25, 0.83 and 0.56 mmol g −1 for Cu(II), Pb(II), Cd(II) and Cr(III), respectively. The adsorption of the four concerned metal ions was hardly affected by common coexisting ions such as Na(I), K(I), Ca(II) and Mg(II), whereas it was slightly decreased when Fe(II) and Zn(II) coexisted in the solution, which illustrates the selective adsorption of Cu(II), Pb(II), Cd(II) and Cr(III) from wastewater. After 10 cycles of adsorption–desorption experiments, there was no significant change in the adsorption capacity, indicating that the polyamine-type starch/GMA copolymer has high adsorption capacity and good reusability.